(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study examines one of the most critical and subtle issues faced by the Algerian War of Liberation between 1954 and 1962: the problem of arms convoys crossing the western Algerian borders to support the armed struggle against French colonialism. These convoys represented the lifeline of the liberation revolution and were given significant attention by the National Liberation Army (ALN). The arms convoys and border crossings encountered severe and complex challenges, primarily in how to penetrate electrified and barbed-wire barriers, avoid landmines, and bypass surveillance towers—particularly from 1957 onward, when crossing the western border became akin to a journey into hell. Despite all these dangers, the ALN succeeded in breaching the borders and ensuring passage, thanks to the continuous development of its methods and techniques for infiltration. It also adapted its organizational and military tactics, which proved successful on numerous occasions.